Effect of applying independence axiom of Axiomatic Design theory on performance of an Integrated Manufacturing Information System: a computer simulation modeling approach. (July 2022) - Mollajan, Ali; Iranmanesh, Hossein; Khezri, AmirHossein; Abazari, Amin
To control manufacturing processes, integration of flows of manufacturing information is an important starting point. In this regard, an effective Integrated Manufacturing Information System (IMIS) which is capable of monitoring, analyzing, and inspecting manufacturing processes properly is critical. Often, most of difficulties in achieving an effective IMIS stem from a poor design for the system architecture. This study particularly addresses the problem of coupling in architecture of an IMIS and its effect on the system performance. This study employs "Independence Axiom" of the Axiomatic Design (AD) theory to deal with the problem and uses "times in process" and "utilized capacities of available resources" as two important criteria for evaluating the system performance. To verify the proposed methodology, a real IMIS is addressed, its stochastic behavior is simulated in Visual SLAM and AweSim (version 3.o) software environment, and the outcomes are analyzed by using logistic regression method for each level of system decomposition. Results of the analyses indicate that fulfillment of independence axiom of AD theory can significantly enhance performance of the concerned IMIS.